Ouvidoria universitária e avaliação institucional: uma análise da proposta do Sistema Nacional de Avaliação do Ensino Superior e das orientações da Controladoria Geral da União - Santos, Edson Xavier dos (2019)
The present research aims to analyze if the Ombudsman from Federal University of Paraiba has acted as an instrument that allows the participation and social control of the academic community in the university management. Thus, the researcher conducted a survey on the evolution of the Brazilian State and the administrative reform, which it went through, including the transition from the bureaucratic State to the managerial one. Reaching the models of democratic and participatory management, in which transparency is a rule of administrative behavior and there is the possibility of exercising social control over the acts of the State by the community, supported by the Access to Information Law. In this context, the public ombudsman, as well as the university ombudsman act as interlocutors between the citizen and the administration. Regarding the adopted methodology, the research was classified as qualitative, based on the phenomenological method, used to investigate the lived experience. Data gathering involved documentary analysis of instructional manuals from the Federal Comptroller General's Office (CGU) and the National System for the Evaluation of Higher Education (SINAES); management reports issued by the Permanent Evaluation Committee (CPA) and the Ombudsman's Office from UFPB; related legislation; as well as the application of semi-structured interviews with teachers, technical-administrative servers, students and the UFPB's ombudsman. To interpret the results, we used the technique of content analysis. The results showed that the UFPB Ombudsman presents problems related to the infrastructure, lack of evaluation of its activities, as well as scarcity of disclosure of its existence and its performance. As a suggestion for improvements, in order to make the UFPB's Ombudsman's Office an instrument of participation and social control available to the academic community, the research proposes the implementation of an effective user evaluation system, stronger advocacy actions that also involve the Administration of the University, change of the room where the Ombudsman works and improvements in its website.